EFEKTIVITAS MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA AUDIOVISUAL TERHADAP HASIL BELAJAR IPAS KELAS V DI SD 3 PAPRINGAN - Amalia Mar’atus Sholikah; Septina Rahmawati; Yoga Awalludin Nugraha; Dhina Cahya Rohim; Devy Aufia Abshor (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of the Contextual Teaching and Learning (CTL) model assisted by audiovisual media on students’ learning outcomes in Science and Social Studies (IPAS) subject for fifth grade students at SD 3 Papringan. The research employed a quasi-experimental method with a Non- equivalent Control Group Design. The sample consisted of 47 students, divided into an experimental class (24 students) and a control class (23 students). Data collection was conducted using pretest and posttest with validated test instruments. Data analysis involved normality test, homogeneity test, independent sample t-test, and N-Gain analysis. The results showed that the experimental class achieved higher learning outcomes compared to the control class. The independent sample t-test yielded a significance value of 0.006 < 0.05, indicating a significant difference between the two groups. Furthermore, the N-Gain analysis revealed that the experimental class achieved an average gain score of 0.6093 (medium category), while the control class achieved 0.4483 (medium category). These findings indicate that the use of CTL with audiovisual media is effective in improving students’ learning outcomes in IPAS. This study suggests that integrating contextual learning approaches with audiovisual support can enhance student engagement and conceptual understanding.